Breeding performance of the Barn Swallow (Hirundo rustica) in a North African urban area: what are the impacts of climatic conditions and insecticide applications? - (:unkn) unknown (My University, 2015)
The present study examined the effects of climate conditions (temperature, precipitation and wind speed) and human activity (insecticide treatment) on clutch size, number of hatchlings and total productivity of the Barn Swallow in a North African urban area (Guelma, Algeria). Our results demonstrated that climatic conditions did not clearly affect reproductive parameters of this Hirundinidae, unlike insecticide treatments inside nesting-buildings. A seasonal decline of the three studied parameters was recorded. The number of hatchlings and total productivity were greater for first than for second clutches. Likewise, productivity significantly decreased in 2013 compared to 2012. Further research on other environmental factors such as: (i) insect availability; (ii) agricultural activity and (iii) adverse weather events, are an essential track for the implementation of management measures to improve local breeding conditions of this North African urban population.
Keywords: African Research